Friendship a philosophical reader - Badhwar, Neera Kapur (London Cornell University Press, 1993)
The 15 essays in this volume provide an overview of the recent philosophical writing about friendship and suggest the unexplored possibilities that friendship offers for philosophical analysis. The first section centers on the nature of friendship, the difference between friendship and other personal loves, and the importance of friendship in the individual's life. The second section discusses the moral significance of friendship and the response of various ethical theories and theorists to the phenomenon of friendship. The last section deals with the importance of personal civic friendship in a good society.
Was Effi Briest a victim of Kantian morality?
Includes bibliographical references and index
ISBN 0-8014-2854-8 (cloth).
Keywords: Friendship